Radiolabeling and Biological Evaluation of Novel 99mTc-Nitrido and 99mTc-Oxo Complexes with 4-Methoxy-L-Phenylalanine Dithiocarbamate for Tumor Imaging - Guangxing Yin; Qing Ruan; Yuhao Jiang; Junbo Zhang (MDPI AG, 2022)
To develop novel radiolabeled amino acid tumor imaging agents, 4-methoxy-L-phenylalanine dithiocarbamate (MOPADTC) was synthesized successfully, and two kinds of 99mTc-labeled complexes ([99mTc]TcN-MOPADTC and [99mTc]TcO-MOPADTC) with high radiochemical purities (RCP > 95%) were obtained. The in vitro stability and partition coefficient were determined, and the results show that both of these complexes have good in vitro stability; [99mTc]TcO-MOPADTC is hydrophilic, while [99mTc]TcN-MOPADTC is slightly lipophilic. The biodistribution of [99mTc]TcN-MOPADTC and [99mTc]TcO-MOPADTC in mice bearing S180 tumors shows that the tumor uptake and tumor/muscle ratio of [99mTc]TcO-MOPADTC were higher than the tumor uptake and tumor/muscle ratio of [99mTc]TcN-MOPADTC. In addition, the tumor retention of [99mTc]TcO-MOPADTC is better than the tumor retention of [99mTc]TcN-MOPADTC. A competitive inhibition assay was performed, and the results indicate that [99mTc]TcO-MOPADTC may enter cells primarily via the L-alanine/L-serine/L-cysteine (ASC) system. Single-photon emission computed tomography (SPECT) imaging of [99mTc]TcO-MOPADTC shows obvious accumulation in tumor sites, suggesting that [99mTc]TcO-MOPADTC is a novel potential tumor-imaging agent.